2016
DOI: 10.1016/j.jos.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular development after open reduction to treat dislocation of the hip after walking age

Abstract: a b s t r a c tBackground: Treatment of hip dislocation diagnosed after walking age is often difficult. We report the surgical treatment of these patients by open reduction with a soft tissue surgical procedure without osteotomy. Methods: Thirty-eight children (43 hips) diagnosed with complete dislocation of the hip after walking age were included in this study. We radiographically analysed postoperative hip joint development up to 6 years of age. To assess the predictors of acetabular development, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…Our findings were similar to previous reports that show~30% of closed reduced hips need future osteotomy. 1,2 Unsatisfactory outcome following open reduction is previously reported as 36% 4 and 49%, 15,16 which is higher than the findings in this study (19% had outcome AI 30). In cases when outcome AI was 30 and no pelvic osteotomy was performed (1 hip in the closed reduction group and 2 hips in the open reduction group; Table 3), the family elected to wait and monitor remodeling.…”
Section: Discussioncontrasting
confidence: 72%
“…Our findings were similar to previous reports that show~30% of closed reduced hips need future osteotomy. 1,2 Unsatisfactory outcome following open reduction is previously reported as 36% 4 and 49%, 15,16 which is higher than the findings in this study (19% had outcome AI 30). In cases when outcome AI was 30 and no pelvic osteotomy was performed (1 hip in the closed reduction group and 2 hips in the open reduction group; Table 3), the family elected to wait and monitor remodeling.…”
Section: Discussioncontrasting
confidence: 72%
“…It should be noted that this study found higher rates of overall residual dysplasia following open and closed reduction than has typically been reported in the literature. 8,9,33,34 In this series, almost 70% of patients showed an AI greater than the 90th percentile at 2 years postoperative. While AI has been shown to improve in hips for up to 7 years postoperatively in patients with satisfactory outcomes, patients with an AI of > 25 degrees at 2 to 4 years have a high likelihood of demonstrating long-term residual dysplasia.…”
Section: Discussionmentioning
confidence: 53%
“…[12] In the present study, the mean age of the patients was 25.09 ± 4.6 months. Kagawa et al [18] evaluated 43 hips of 38 children with Tönnis grade 3 and 4 hip displacements treated by an OR after walking age. In their study, it was observed that radiologically the hip joint development continued to improve until 6 years and, in some cases, up to 7-8 years.…”
Section: Discussionmentioning
confidence: 99%